Global Navigation Satellite System ambiguity decorrelation through diagonal elements precomputing and ordering method. Issue 1 (1st January 2013) - Yanxin, Yao; Fan, Ding
Abstract : Integer ambiguity decorrelation has long been an important problem for global navigation satellite system high‐precision relative positioning applications for its effect of deducing search number of candidate integer ambiguities. It is difficult to design a decorrelation method with fine performance. Among those decorrelation methods based on LDL T decomposition, direct‐ordering method (DOM) is the one that follows the principle of ordering diagonal elements of variance–covariance matrix before decorrelation. In the present study, the authors propose a diagonal element precomputing and an ordering method (DEPOM) based on LDL T . DEPOM orders diagonal elements of the matrix according to values after LDL T decomposition, in contrast to DOM according to values before LDL T decomposition. Thus, DEPOM is closer to the aim of arranging the larger diagonal element to the larger row before decomposition. The nodus is to determine elements in decomposed L and D matrices, which constitutes an improved LDL T decomposition method. The above study show that DEPOM has better decorrelation degree and a higher success rate than DOM from the numerical simulation tests. The performance of DEPOM is equivalent to the united ambiguity decorrelation method. However, it is different. DEPOM is a supplement to the integer least‐squares theory. The improved LDL T decomposition is also a new form in the LDL T decomposition family.